Health economic analysis of a cluster‐randomised trial (OptiBIRTH) designed to increase rates of vaginal birth after caesarean section. (7th April 2019) - Fobelets, M; Beeckman, K; Healy, P; Grylka‐Baeschlin, S; Nicoletti, J; Devane, D; Gross, MM; Morano, S; Daly, D; Begley, C; Putman, K
Abstract : Objective: To perform a health economic analysis of an intervention designed to increase rates of vaginal birth after caesarean, compared with usual care. Design: Economic analysis alongside the cluster‐randomised OptiBIRTH trial (Optimising childbirth by increasing vaginal birth after caesarean section (VBAC) through enhanced women‐centred care). Setting: Fifteen maternity units in three European countries – Germany (five), Ireland (five), and Italy (five) – with relatively low VBAC rates. Population: Pregnant women with a history of one previous lower‐segment caesarean section; sites were randomised (3:2) to intervention or control. Methods: A cost–utility analysis from both societal and health‐services perspectives, using a decision tree. Main outcome measures: Costs and resource use per woman and infant were compared between the control and intervention group by country, from pregnancy recognition until 3 months postpartum. Based on the caesarean section rates, and maternal and neonatal morbidities and mortality, the incremental cost–utility ratios were calculated per country. Results: The mean difference in costs per quality‐adjusted life years (QALYs) gained from a societal perspective between the intervention and the control group, using a probabilistic sensitivity analysis, was: €263 (95% CI €258–268) and 0.008 QALYs (95% CI 0.008–0.009 QALYs) for Germany, €456 (95% CI €448–464) and 0.052 QALYs (95% CI 0.051–0.053 QALYs) for Ireland, and €1174 (95% CI €1170–1178) and 0.006 QALYs (95% CI 0.005–0.007 QALYs) for Italy. The incremental cost–utility ratios were €33, 741/QALY for Germany, €8785/QALY for Ireland, and €214, 318/QALY for Italy, with a 51% probability of being cost‐effective for Germany, 92% for Ireland, and 15% for Italy. Conclusion: The OptiBIRTH intervention was likely to be cost‐effective in Ireland and Germany. Tweetable abstract: The OptiBIRTH intervention (to increase VBAC rates) is likely to be cost‐effective in Germany and Ireland. Tweetable abstract: The OptiBIRTH intervention (to increase VBAC rates) is likely to be cost‐effective in Germany and Ireland.